Effective Utilization of Coal Processing Waste: Separation of Low Ash Clean Coal from Washery Rejects by Hydrothermal Treatment. (17th February 2022) - Sriramoju, Santosh Kumar; Babu, Varahala; Dash, Pratik Swarup; Majumdar, Saptarshi; Shee, Debaprasad
ABSTRACT: Handling and disposal of high volume of fine coal tailings is a biggest challenge for coal washeries. Separation of clean coal by density separation and flotation shows limited yields of 23–28% and 13–14% respectively. Chemical leaching process has a challenge with the formation of insoluble salts. The present investigation aimed to separate clean coal by a combination of chemical-physical separation technique, i.e. alkaline hydrothermal process followed by density separation. Hydrothermal extraction of humic substance causes dissociation of coal aggregated structure (Mineral-Maceral-Pore structure), thus improves the separation. Experiments performed as per design of experiments and reduced design of experiments, where 100 µ particle size, 50% (w/w) pulp density, 4.5% KOH (w/w), and 140°C reaction temperature found to be optimum, at which 16.2% ash clean coal at 40.7% yield and humic acid by-product at 18.3% yield were obtained. Use of swelling agent such as tetrahydrofuran shown negative impact on clean coal recovery. Material balance and cost data were presented to show the techno-commercial viability of this technology.